FINANCIAL GLOBALIZATION AND FINANCIAL SECTOR DEVELOPMENT IN NIGERIA - Adedeji Daniel Gbadebo (J-MACC, 2025)
Financial globalisation requires serious consideration in an effort to stimulate financial development of any economy. Despite the governmental measures to improve financial globalisation, the sector still experiences low level of development in Nigeria. This study investigated the impact of financial globalization on financial sector development in Nigeria. Ex-post facto design was employed and annual data were obtained from the World Bank's Development Indicators and Global Financial Development Database from 1981 to 2023. Autoregressive distributed lag (ARDL) method was used for data analysis. Financial globalisation index was found to have had positive effect on money market development both in the short-run (=0.153; p<0.01) and long run(=0.349;p<0.01). A positive effect was also reported for capital market development, but only in the long run (=6.217; p<0.01). The study concluded that financial globalization levels are low in Nigeria and there has been little improvement in its levels over the period. The study recommended that the Nigerian authority should direct policy attention to promoting increased globalization of the financial sector through further deregulation of its activities and removal of restrictions on actors in this sector.